History of the Alaydrus Dynasty, Founder of the Kubu Sultanate in West Kalimantan in the XVIII-XIX centuries AD - Ridwan, Ridwan; Hasibuan, Samsul Bahri; Fauzan, Rizal; Supendi, Usman; Thohir, Ajid (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This article aims to explain the history of the Alaydrus dynasty, founder of the Kubu Sultanate in West Kalimantan in the 18th-19th centuries AD. The method used is a historical method, while the sources used are a colonial article entitled Borneo's Wester Afdeeling which was published in 1854 AD by Pieter Johannes Veth, then Geneology and the Adventures of Syarif Idrus Alaydrus which was published by the Alaydrus family, and other secondary books. The result of the discussion in this article is that the Kubu Sultanate was founded by Syarif Idrus Alaydrus and had the title Tuan Besar Sultan Kubu. The Alaydrus dynasty itself is a family name in Hadramaut, Yemen. Alaydrus belonged to the Ba' Alawi tribe, descendants of Husein ra, in the 15th century AD. Sultans who once led the Kubu Sultanate included: Syarif Idrus bin Abdurrahman Alaydrus, Syarif Muhammad bin Idrus Alaydrus, Syarif Abdurrahman bin Muhammad Alaydrus, Syarif Ismail bin Abdurrahman Alaydrus, etc. In 1953 the Kubu Sultanate ended and became part of the Unitary State of the Republic of Indonesia.